Managing Global Supply Chain: The Sports Footwear, Apparel and Retail Sectors - Mamic, Ivanka (Journal of business ethics, 2005)
Amongst a backdrop of debate regarding Codes of Conduct and their raison d’etre this paper provides a detailed summary of the management systems used by multinational enterprises in the Code implementation process. It puts forth a framework for analysis based on the elements of – the creation of a vision, the development of understanding and ability, integration into operations and feedback, improvement and remediation – and then applies it across the sports footwear, apparel and retail sectors in order to firstly, demonstrate the complexities of the Code implementation process and secondly, to provide useful examples and lessons-learned to companies, policy-makers and others interested in implementing their own Code of Conduct or who are actively involved in this field.